Генофонд та перспективи селекції Persica Mill. у НБС ім. М.М. Гришка НАН України - Голубкова, І.М. (Фактори експериментальної еволюції організмів, 2016)
Aim. Select perspective donors of a peach by agriculturally important characteristics, resistance to the conditions of the Forest-steppe ecoregion of Ukraine. Methods. The complex evaluation of grades and hybrids of a peach was performed coresponding to standard methods and techniques. Results. The characteristic of a gene pool of peach collection of M.M. Grishko NBG allowed to define perspective exponents of a peach that has the increased adaptation to stressful factors of environment and stores its taste. Conclusions. It was established that the main donor to abiotic and biotic factors of environment is – the Suputnyk; on a large-fruited – Pamyat Grishko, Podarok Kieva, Dniprovskiy, 122 ГЛ; early terms of fructification – Zheltoplodniy ranniy, Antocyanoviy, Lesostepnoy, Iyulsky 14Л; late terms of flowering – Rumyanyi, Osennij Surpris, Antocianoviy, Lyubimez, Kievskiy Surpriz, Podarok Kieva, 811 K, 810 S.V., 77 K, 86 M, etc. Keywords: peach, genofond, hybrids, cultivar, donors.